Beneficial effect of kidney transplantation from a deceased donor on severe chronic refractory intradialytic hypotension – a case report - Ewa Ignacak; Dominik Cieniawski; Alina Bętkowska-Prokop; Czesław Osuch; Marek Kuźniewski; Władysław Sułowicz (BMC Nephrology, 2017)
Abstract Background Chronic refractory hypotension (IDH, intradialytic hypotension) is a rare but serious problem encountered in patients on hemodialysis. Patients with chronic hypotension are often disqualified by transplant teams from renal transplantation. This is due to the possibility of an enormous risk of ischemic complications. Case presentation We describe a 44-year old female patient with severe refractory hypotension (mean BP 60/30 mmHg, the lowest 48/28 mmHg), which appeared after bilateral laparoscopic nephrectomy of the infected kidneys. The kidney transplantation from a deceased donor, with infusion of the two pressor amines (dopamine, dobutamine) was performed without technical complications and the blood pressure measurements were 100–120/70–80 mmHg. The immunosuppression regimen was tacrolimus (TAC) + mycophenolate mophetil (MMF) and steroids (GS). Pressor amines were discontinued on the 18th day after the transplantation. Because of delayed graft function, 4 hemodialysis treatments were performed. The patient was discharged from the hospital on the 22nd day with good function of the transplanted kidney (the concentration of serum creatinine 117 μmol/l). During one-year follow-up, the patient has been remaining stable with a very good graft function (serum creatinine 84 μmol/l) and normal blood pressure (115/70 mmHg). Conclusions Proper preparation and adequate perioperative treatment allowed for safely performing kidney transplantation in the patient with severe IDH.